Low on-clopidogrel ADP- and TRAP-6-induced platelet aggregation in patients with atrial fibrillation undergoing percutaneous coronary intervention: an observational pilot study - Gjermeni, Diona; Anfang, Viktoria; Vetter, Hannah; Szabó, Sofia; Hesselbarth, David; Gauchel, Nadine; Siegel, Patrick Malcolm; Kaier, Klaus; Kille, Alexander; Franke, Kilian Friedrich Wilhelm; Leggewie, Stefan; Trenk, Dietmar; et al. (Journal of thrombosis and thrombolysis, 2024)
High on-clopidogrel platelet reactivity (HPR) associates with ischemic risk in patients after percutaneous intervention (PCI). This study aimed to evaluate the association of HPR as assessed by multiple electrode aggregometry (MEA) with ischemic, thromboembolic, and bleeding risk in patients with atrial fibrillation (AF) undergoing PCI. Patients with AF and an indication for oral anticoagulation (OAC) were included in this prospective cohort study on day 1-3 after PCI. Platelet aggregation [U] was analyzed by MEA. HPR and low platelet reactivity (LPR) were defined as ADP-induced aggregation ≥ 46 U and ≤ 18 U, respectively. TRAP-6-induced aggregation reference was 94-156 U. The primary outcome was time to all-cause death, myocardial infarction, or stroke at 6 months. The secondary outcome was time to non-major clinically relevant bleedings or major bleedings. 159 patients were enrolled between May 2020 and May 2021. The median age was 78 years (interquartile range 72-82) and 111 (70%) were male. Median ADP- and TRAP-induced aggregation were 12 (6-17) and 49 (35-68) U, respectively. 147 (93%) patients had a low overall aggregability. HPR was detected in 2 patients (1%) and 125 (79%) had LPR. ADP-induced aggregation did not significantly associate with the primary outcome (r = 0.081, p = 0.309) but correlated inversely with bleeding risk (r = − 0.201, p = 0.011). HPR status as assessed by MEA among patients with AF after PCI was rare and overall aggregability was low. Conventional cut-off values for HPR might be inappropriate for these patients. ADP-induced aggregation might be helpful to identify patients at risk for bleeding.
Gesehen am 18.06.2024